THE INFLUENCE OF Co-Ni/Al2O3 SYSTEMS SYNTHESIS METHOD ON THEIR CATALYTIC ACTIVITY IN THE REACTION OF СО2 METHANATION: UDC 544.47:544.344+546.73+546.74+546.264-31 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
The series of Co-Ni catalysts supported onto Al2O3 was synthesized by different methods: nitrate decomposition, citrate decomposition and reduction in the emulsion. All catalysts were tested in the reaction of СО2 methanation. The highest catalytic activity was obtained from the samples of nitrate decomposition series. Co-enriched samples (Со60Ni40, Со80Ni20, Со100) from this series showed 100 % of СО2 conversion at the lower temperature (300°С) compared to other series. Desorption of СН4 (m/z = 16), СН3* (m/z = 15) and СОН* (m/z = 29) particles from the surface of active samples at the high temperature (400–500 °С) was registered with the method of TPD MS. Possibly, the mechanism of СО2 methanation includes the formation of intermediate CHO* compound. A complicate surface structure of Со80Ni20/Al2O3 sample with the high catalytic activity was demonstrated by the scan electronic microscopy. The size range of particles was 10-100 μm and the middle size was 30 μm. XRD analysis of Co80Ni20/Al2O3 та Co60Ni40/Al2O3 samples shoved the presence of carrier phase: corundum (Al2O3), boehmite AlO(OH), cubic γ-Al2O3. Also phases of spinel (Co3O4) and cubic phase of metal (Co, Ni or their alloy) were indentified. Reflections of spinel are wide and low indicating their nanosize. Reflections of metal are narrow and intensive, indicating the large size of metal crystal.
Keywords: СО2 methanation; catalytic activity; Co-Ni/Al2O3 catalysts; nitrate decomposition